Analisis Kemiskinan Dan Pertumbuhan Ekonomi Di Indonesia - Rizki Lailatul Illahi; Sri Ulfa Sentosa (Media Riset Ekonomi Pembangunan (MedREP), 2025)
This study aims to analyze two main aspects: (1) the impact of economic growth, unemployment, health, and internet access on poverty in Indonesia, and (2) the influence of poverty, labor force, and education on economic growth. The research employs a descriptive and inductive approach with multiple linear regression analysis using the Two-Stage Least Squares (2SLS) method on time series data from 1992 - 2022. Secondary data were obtained from the Central Bureau of Statistics (BPS), with dependent variables consisting of poverty and economic growth, while independent variables include unemployment, health, internet access, labor force, and education.